Neighbourhood Nuisances in The Bahamas: The Case of New Providence - Adderley, Cassandra R. (International Journal of Bahamian Studies, 2008)
This paper discusses the issue of neighbourhood nuisances in The Bahamas using New Providence as a case study. Despite there being a legal framework that defines actions which are classified as nuisances, and thereby defines actions which are illegal, it is apparent that most residents suffer from nuisances in their neighbourhoods. Results from a convenience sample of 414 adults living in New Providence, show that residents are very tolerant of nuisances and rarely involve the police, even when the activity is criminal. It is hypothesized that residents’ tolerance to nuisances arises from a complex interaction of innate tolerance, apathy and a feeling that the police are ineffective. In common with studies done elsewhere, noise was the biggest nuisance to most people; this may suggest that revised legislation is required to mitigate this pervasive social ill.